A Case of CCDC6-RET Fusion Mutation in Adult Acute Lymphoblastic Leukemia (ALL), a Known Activating Mutation Reported in ALL - Mejia Saldarriaga, Mateo; Steinberg, Amir; Severson, Eric A.; Binder, Adam (Frontiers in Oncology, 2019)
We report the case of a patient with acute lymphoblastic leukemia (ALL) who was found to have a gene fusion involving the CCDC6 and RET genes. Although the RET gene has been identified before extensively as an oncogene, it is the first time it is identified in this neoplasm. Using a wide comprehensive genomic profiling assay (FoundationOneHeme®), the CCDC6-RET fusion gene was identified and considered to be a driver mutation given the lack of alternative driver mutations known to have a central role in ALL. The identification of known fusion genes conferring activating tyrosine kinase activity in neoplasms can suggest potential therapeutic role of tyrosine kinase inhibitors (TKI), an approach that has been exploited in several other fusions gens and neoplasms harboring RET mutations.